Lobbying Hitler : industrial associations between democracy and dictatorship - Bera, Matt (Berghahn Books, 2016)
"This book focuses on two major industrialists and their respective industries during the rise and governance of the National Socialist party: Jakob Reichert (iron and steel) and Karl Lange (machine building)"